The Effect of Maternal Multiple Micronutrient Supplementation on Cognition and Mood during Pregnancy and Postpartum in Indonesia: A Randomized Trial - Prado, Elizabeth L. (Public Library of Science, 2012)
Maternal caregiving capacity, which is affected in part by cognition and mood, is crucial for the health of mothers and infants. Few interventions aim to improve maternal and infant health through improving such capacity. Multiple micronutrient (MMN) supplementation may improve maternal cognition and mood, since micronutrients are essential for brain function. We assessed mothers who participated in the Supplementation with Multiple Micronutrients Intervention Trial (SUMMIT), a double-blind cluster-randomized trial in Indonesia comparing MMN supplementation to iron and folic acid (IFA) during pregnancy and until three months postpartum. We adapted a set of well-studied tests of cognition, motor dexterity, and mood to the local context and administered them to a random sample of 640 SUMMIT participants after an average of 25 weeks (SD = 9) of supplementation. Analysis was by intention to treat. Controlling for maternal age, education, and socio-economic status, MMN resulted in a benefit of 0.12 SD on overall cognition, compared to IFA (95%CI 0.03–0.22, p = .010), and a benefit of 0.18 SD on reading efficiency (95%CI 0.02–0.35, p = .031). Both effects were found particularly in anemic (hemoglobin<110 g/L; overall cognition: B = 0.20, 0.00–0.41, p = .055; reading: B = 0.40, 0.02–0.77, p = .039) and undernourished (mid-upper arm circumference<23.5 cm; overall cognition: B = 0.33, 0.07–0.59, p = .020; reading: B = 0.65, 0.19–1.12, p = .007) mothers. The benefit of MMN on overall cognition was equivalent to the benefit of one year of education for all mothers, to two years of education for anemic mothers, and to three years of education for undernourished mothers. No effects were found on maternal motor dexterity or mood. This is the first study demonstrating an improvement in maternal cognition with MMN supplementation. This improvement may increase the quality of care mothers provide for their infants, potentially partly mediating effects of maternal MMN supplementation on infant health and survival. The study is registered as an International Standard Randomized Controlled Trial, number ISRCTN34151616. http://www.controlled-trials.com/ISRCTN34151616